Environmental stress and nanoplastics’ effects on Ciona robusta: regulation of immune/stress-related genes and induction of innate memory in pharynx and gut - Marino, Rita; Melillo, Daniela; Italiani, Paola; Boraschi, Diana (Frontiers in Immunology, 2023)
The immune system of the solitary ascidian Ciona robusta relies on two organs, the pharynx and the gut, and encompasses a wide array of immune and stress-related genes. How the immune system of C. robusta reacts and adapts to environmental stress was assessed upon short or long exposure to hypoxia/starvation in the absence or in the presence of polystyrene nanoplastics. We show that the immune response to stress is very different between the two organs, suggesting an organ-specific immune adaptation to the changes in the environmental conditions. Notably, the presence of nanoplastics appears to alter the gene modulation induced by hypoxia/starvation in both organs, resulting in a partial increase in gene up-regulation in the pharynx and a less evident response to stress in the gut. We have also assessed whether the hypoxia/starvation stress could induce innate memory, measured as gene expression in response to a subsequent challenge with the bacterial agent LPS. Exposure to stress one week before challenge induced a substantial change in the response to LPS, with a general decrease of gene expression in the pharynx and a strong increase in the gut. Co-exposure with nanoplastics only partially modulated the hypoxia/starvation stress-induced memory response to LPS, without substantially changing the stress-dependent gene expression profile in either organ. Overall, the presence of nanoplastics in the marine environment seems able to decrease the immune response to C. robusta to stressful conditions, hypothetically implying a reduced capacity to adapt to environmental changes, but only partially affects the stress-dependent induction of innate memory and subsequent responses to infectious challenges.